Manual of botulinum toxin therapy - Truong, Daniel (Daniel D.); Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
Fully updated throughout, the second edition of the Manual of Botulinum Toxin Therapy provides practical guidance on the use of Botox in a wide variety of disorders. New chapters have been added on the use of botulinum toxin in wound healing, in focal hand dystonia and in thoracic outlet syndrome, as well as others. There are new chapters on the use of botulinum toxins in conjunction with ultrasound guidance. Using clear line-drawings the Manual describes the relevant injection sites for each condition and gives comparative dosage tables for the various formulations of toxins used in different muscle groups. Throughout the emphasis is on technique and the book can be used as both a teaching aid and in bedside guidance. The manual will be of use to neurologists, otolaryngologists, urologists, ophthalmologists, dermatologists, internists, pain management specialists, rehabilitation specialists and plastic surgeons, and any other clinicians discovering the potential of botulinum toxin.
Contents note continued: 15. The use of botulinum neurotoxin in spastic infantile cerebral palsy / H. Kerr Graham -- 16. The role of ultrasound for botulinum neurotoxin injection in childhood spasticity / Bettina Westhoff -- 17. The use of botulinum neurotoxin in spasticity using ultrasound guidance / Pietro Fiore -- 18. The use of botulinum neurotoxin in tic disorders and essential hand and head tremor / Joseph Jankovic -- 19. Treatment of stiff-person syndrome with botulinum neurotoxin / Bahman Jabbari -- 20. Botulinum neurotoxin applications in ophthalmology / Alan Scott -- 21. Cosmetic uses of botulinum neurotoxins / Christopher Zachary -- 22. Hyperhidrosis / Markus K. Naumann -- 23. Botulinum neurotoxin A treatment for ischemic digits / Kelli Webb -- 24. Botulinum neurotoxin in wound healing / Holger G. Gassner -- 25. Use of botulinum neurotoxin in neuropathic pain / Chaur-Jong Hu -- 26. The use of botulinum neurotoxin in the management of headache disorders / Stephen D. Silberstein.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Neurotoxic agents -- Therapeutic use; Movement disorders -- Treatment; Neuromuscular diseases -- Treatment; Botulinum toxin -- Therapeutic use; Electronic books